PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI BALAI BESAR METEOROLOGI KLIMOTOLOGI DAN GEOFISIKA WILAYAH II CIPUTAT TIMUR TANGERANG SELATAN - Muhammad Faqih (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Work Environment (X1) and Motivation (X2) on Employee Performance (Y) at BMKG Region II. This study uses quantitative research with descriptive methods. The number of samples used in this study was 80 respondents. The data collection technique used was a questionnaire and data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that the Work Environment (X1) has a significant effect on Employee Performance (Y) with a determination coefficient value of 58.8% and the hypothesis test obtained tcount> ttable (10.559> 1.990). Motivation (X2) has a significant effect on Employee Performance (Y) with a determination coefficient value of 65.1% and the hypothesis test obtained tcount> ttable (12.052> 1.990). The Work Environment (X1) and Motivation (X2) simultaneously have a significant effect on Employee Performance (Y) with a regression equation Y = 3.966 + 0.767 (X1) + 0.809 (X2). The coefficient of determination value is 73.0%. Hypothesis testing shows that Fcount > Ftable, namely (104.217 > 3.12).